Gut microbiome alterations induced by tributyltin exposure are associated with increased body weight, impaired glucose and insulin homeostasis and endocrine disruption in mice. (November 2020) - Zhan, Jing; Ma, Xiaoran; Liu, Donghui; Liang, Yiran; Li, Peize; Cui, Jingna; Zhou, Zhiqiang; Wang, Peng
Abstract: Tributyltin (TBT), an organotin compound once widely used in agriculture and industry, has been reported to induce obesity and endocrine disruption. Gut microbiota has a strong connection with the host's physiology. Nevertheless, the influences of TBT exposure on gut microbiota and whether TBT-influenced gut microbiota is related to TBT-induced toxicity remain unclear. To fill these gaps, ICR (CD-1) mice were respectively exposed to TBT at NOEL (L-TBT) and tenfold NOEL (H-TBT) daily by gavage for 8 weeks in the current study. The results showed that TBT exposure significantly increased body weight as well as epididymal fat, and led to adipocyte hypertrophy, dyslipidemia and impaired glucose and insulin homeostasis in mice. Additionally, TBT exposure significantly decreased the levels of T4, T3 and testosterone in serum. Also of note, TBT exposure changed gut microbiota composition mainly by decreasing Bacteroidetes and increasing Firmicutes proportions. To confirm the role of gut microbiota in TBT-induced overweight and hormonal disorders, fecal microbiota transplantation was performed and the mice receiving gut microbiota from H-TBT mice had similar phenotypes with their donor mice including significant body weight and epididymal fat gain, glucose and insulin dysbiosis and hormonal disorders. These results suggested that gut microbiome altered by TBT exposure was involved in the TBT-induced increased body weight, impaired glucose and insulin homeostasis and endocrine disruption in mice, providing significant evidence and a novel perspective for better understanding the mechanism by which TBT induces toxicity. Graphical abstract: Image 1 Highlights: TBT exposure at NOEL and tenfold NOEL doses caused body weight and fat mass gain in mice. TBT could disrupt thyroid hormones and testosterone in mice. TBT exposure resulted in changes to gut microbiota composition in mice. TBT-driven microbiota transplant resulted in body weight gain and endocrine disruption in antibiotic-treated mice. Abstract : Summary: TBT-altered gut microbiota is associated with increased body weight, impaired glucose and insulin homeostasis and endocrine disruption in mice.